Phase 1/2 study to assess the safety, efficacy, and pharmacokinetics of barasertib (AZD1152) in patients with advanced acute myeloid leukemia - Löwenberg, Bob (American Society of Hematology, 2011)
The primary objective of this 2-part phase 1/2 study was to determine the maximum-tolerated dose (MTD) of the potent and selective Aurora B kinase inhibitor barasertib (AZD1152) in patients with newly diagnosed or relapsed acute myeloid leukemia (AML). Part A determined the MTD of barasertib administered as a continuous 7-day infusion every 21 days. In part B, the efficacy of barasertib was evaluated at the MTD. In part A, 32 patients were treated with barasertib 50 mg (n = 3), 100 mg (n = 3), 200 mg (n = 3), 400 mg (n = 4), 800 mg (n = 7), 1200 mg (n = 6), and 1600 mg (n = 6). Dose-limiting toxicities (stomatitis/mucosal inflammation events) were reported in the 800 mg (n = 1), 1200 mg (n = 1), and 1600 mg (n = 2) groups. The MTD was defined as 1200 mg. In part B, 32 patients received barasertib 1200 mg. In each part of the study, 8 of 32 patients had a hematologic response according to Cheson AML criteria. The most commonly reported grade ≥ 3 events were febrile neutropenia (n = 24) and stomatitis/mucosal inflammation (n = 16). We concluded that the MTD of barasertib is 1200 mg in patients with relapsed or newly diagnosed AML. Toxicity was manageable and barasertib treatment resulted in an overall hematologic response rate of 25%. This study is registered at www.ClinicalTrials.gov as NCT00497991.